Factors influencing whether students choose STEM high school programs: a quantitative study of a selection of factors - Marcus, Landahl (My University, 2023)
In this study, several factors that may influence a student's choice of pursuing a STEM high school program was studied. The factors studied are some of those identified and studied in previous research in this field. A survey was conducted with students in grade 9 in five different schools. The data collected was analysed and statistical methods were applied to find possible correlations and effect sizes. The results showed that parental educational background could not be shown to have a statistically significant effect. Self-efficacy was found to be the strongest influence in terms of difference in means and effect size. Other factors that were studied and found to be significant were gender, interest in STEM subjects in school as well as other STEM topics, attitude towards STEM education and science & technology in society and lastly a student's future desired profession.